The Equity Risk Premium: Empirical Evidence from Emerging Markets - Michael Donadelli; Lorenzo Prosperi (LUISS Guido Carli, Department of Economics and Business, Arcelli Centre for Monetary and Financial Studies, 2012)
The analysis of the Equity Risk Premium (ERP) and the research efforts aimed at solving the Equity Premium Puzzle (Mehra and Prescott 1985), are still widely discussed in the economic and financial literature. The purpose of this paper is to show that differences in the ERP between developed and emerging markets lead to many empirical asset pricing issues. Using data from both markets, we first provide an ex-post simple time series analysis on the ERP. Compared to developed markets, and in line with existing literature, we find that emerging markets compensate investors with higher returns. We observe that the time varying nature of the ERP in emerging economies, relates mainly to economic cycles, shocks and other macro phenomena (i.e. global financial market integration). Basic statistics also show that during the last decade the ERP shrunk, especially in advanced economies. To improve investigations on the higher emerging markets' equity premium, a standard global asset pricing model is adopted. On one hand, we mainly find that the one-factor model does not fully predict emerging markets' equity premia. On the other hand, we discover that the inclusion of liquidity conditions and time-varying components provides reasonable explainations for the behaviour of equity premia in these 'young' markets. Our final findings mainly suggests that global business cycle and financial integration process are crucial in determining the risk associated to emerging markets' investments.
Keywords: C13; G12; G15; E44; 330; Stock markets returns; equity premium puzzle; Equity risk premium